Laparoendoscopic single-site cholecystectomy and common bile duct exploration using conventional instruments. (September 2016) - Tian, Yu; Wu, Shuodong; Chen, Chun-Chih; Chen, Yongsheng
Abstract: Background: Optimization of quality of life is an important goal in the advanced surgery. Herein we share our fifteen cases to demonstrate the feasibility of scarless laparoendoscopic single-site common bile duct (CBD) exploration using conventional instruments in the management of CBD stones. Methods: Fifteen patients (4 male) underwent transumbilical laparoendoscopic single-site cholecystectomy and CBD exploration: the patients were diagnosed with CBD stones. The endoscopic nasobiliary drainage (ENBD), endoscopic retrograde biliary drainage (ERBD) or J-type tube was introduced into the CBD preoperatively or intraoperatively. A 2-cm periumbilical incision was made for the placement of three trocars. Conventional rigid laparoscopic instruments were solely used throughout the procedure, and operative techniques were carried out in the same fashion as for conventional T-tube-free laparoscopic cholecystectomy and CBD exploration. Results: The procedures were completed uneventfully in the mean duration of 125.7 min. Three patients occurred pigtail J-tube displacement and all three were later excreted safely in stool. Conclusions: Laparoendoscopic single-site cholecystectomy and CBD exploration appears to be a technically feasible alternative to standard laparoscopic procedure, and can be performed using conventional laparoscopic instruments. Laparoscopic primary closure with preoperative ENBD and ERBD tubes and with intraoperative J-tubes is safe and feasible. Highlights: Fifteen patients underwent laparoendoscopic single-site cholecystectomy and common bile duct exploration. The patients were diagnosed with common bile duct stones. The ENBD, ERBD or J-type tube was introduced into the common bile duct preoperatively or intraoperatively. All patients completed the surgery with T-tube-free procedures without any major complications including residual stones.